If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5(5x + -1) = -113 Reorder the terms: 2x + 5(-1 + 5x) = -113 2x + (-1 * 5 + 5x * 5) = -113 2x + (-5 + 25x) = -113 Reorder the terms: -5 + 2x + 25x = -113 Combine like terms: 2x + 25x = 27x -5 + 27x = -113 Solving -5 + 27x = -113 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 27x = -113 + 5 Combine like terms: -5 + 5 = 0 0 + 27x = -113 + 5 27x = -113 + 5 Combine like terms: -113 + 5 = -108 27x = -108 Divide each side by '27'. x = -4 Simplifying x = -4
| 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r | | v=25(30) | | -2x+17=8+x | | -12r-48=12 | | -(5-3x)-6(2x-4)=x+1 | | 24x^4=36x^3-12x^2/12x^2 |